Pengaruh Model Pembelajaran Project Based Learning Terintegrasi STEM Terhadap Pemahaman Konsep Fisika Siswa di SMAN 1 X Koto Tanah Datar - Utia, Rahimatul; Yurnetti, Yurnetti; Hidayati, Hidayati; Novitra, Fuja (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to find out the influence of the Integrated Project Based Learning learning model of the Science Technology Engineering and Mathematics (STEM) approach on the understanding of physics concepts of grade X students of SMAN 1 X Koto Tanah Datar. This study was carried out using a quantitative method with the Quasy Experiment type. The research instrument is in the form of a multiple-choice test with 5 choices. Before the test is given, the instrument will be tested for validity, reliability, difficulty, and differentiation. A total of 67 students of Class X Phase E became the study sample, namely 32 students from the experimental group and 35 students from the control group. The methods used to analyze the data include homogeneity tests, normality tests, and hypothesis tests. The findings of the study in the hypothesis test showed a significance value of < 0.05 which means that the use of the STEM integrated PjBL learning model affects the understanding of physics concepts of grade X students of SMAN 1 X Koto Tanah Datar.